2017
DOI: 10.1016/j.burns.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Not all patients meet the 1 day per percent burn rule: A simple method for predicting hospital length of stay in patients with burn

Abstract: Traditional LOS estimates of 1day/%TBSA burn rule is biased, underestimating LOS, particularly for patients >40 years with inhalation injury. The following formulas applied at admission can accurately estimate hospital LOS, improve prediction over 1day/%TBSA, and provide results comparable to complicated models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 8 publications
3
22
0
Order By: Relevance
“…The most significant prognostic factor providing the highest discharge ratios in all children was %TBSA, similar to previous research (Dolp et al 2018;Möller et al 2017;Hussain and Dunn 2013;AbdelWahab et al 2018;Taylor et al 2017;Gravante et al 2007;Matin et al 2015;Elrod et al 2019;Wang et al 2018;Hyland et al 2015;Meshulam-Derazon et al 2006). In Aboriginal and Torres Strait Islander children, greater %TBSA levels have been reported to increase LOS, however our ratios were greater than previous reports (Möller et al 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The most significant prognostic factor providing the highest discharge ratios in all children was %TBSA, similar to previous research (Dolp et al 2018;Möller et al 2017;Hussain and Dunn 2013;AbdelWahab et al 2018;Taylor et al 2017;Gravante et al 2007;Matin et al 2015;Elrod et al 2019;Wang et al 2018;Hyland et al 2015;Meshulam-Derazon et al 2006). In Aboriginal and Torres Strait Islander children, greater %TBSA levels have been reported to increase LOS, however our ratios were greater than previous reports (Möller et al 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Internationally there is a sound body of knowledge surrounding prognostic factors for hospital LOS in burn injuries (Dolp et al 2018;Moore et al 2015;Hussain and Dunn 2013;AbdelWahab et al 2018;Taylor et al 2017;Gravante et al 2007;Sierra Zúñiga et al 2016;Matin et al 2015;Elrod et al 2019;Wang et al 2018). In adults, percentage total body surface area (%TBSA), full thickness burns, socioeconomic status (SES), age, inhalation injury, comorbidities, surgical interventions, and injury complications have been shown to be associated with a longer LOS (Dolp et al 2018;Moore et al 2015;Hussain and Dunn 2013;AbdelWahab et al 2018;Taylor et al 2017;Gravante et al 2007;Sierra Zúñiga et al 2016). In children with a burn injury, large %TBSA (> 16%), burn cause (scald or flame compared to other types), full and partial thickness burns increase LOS, whereas younger age and early skin grafting decrease LOS (Matin et al 2015;Elrod et al 2019;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ARDS only effected LOS in the ICU and not inpatient units [30]. In our initial non-matched analysis, inhalation injury was an associated factor with increased LOS, a finding that parallels the recent large-scale record review of the American Burn Association (ABA) National Burn Repository [8]. However, in our matched analysis that association was lost as the presence of inhalation injury resulted in equal number of patients having expected-LOS and exceeding-LOS.…”
Section: Discussionsupporting
confidence: 66%
“…The LOS prediction solely based on the TBSA% has been under heavy critique for inaccuracy, and newer prediction models try to take into account the complexity of burn injury by incorporating variables of inhalation injury and age [8]. It has been postulated that a precise LOS prediction needs to include pre-existing medical conditions, demographics, and directly burn-related variables such as %TBSA and inhalation injury, but also complications that develop during hospitalization [8, 9]. However, it is still unclear to what extent medical conditions contribute to an increase in LOS in burn patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation